A systematic review of the cost-effectiveness of anti-VEGF drugs for the treatment of diabetic retinopathy - Robert Hodgson; Matthew Walton; Helen Fulbright; Laura Bojke; Ruth Walker; Alexis Llewellyn; Sofia Dias; Lesley Stewart; David Steel; John Lawrenson; Tunde Peto; Mark Simmonds (Health Technology Assessment)
Background Non-proliferative and proliferative diabetic retinopathy are common complications of diabetes and a major cause of sight loss. Anti-vascular endothelial growth factor drugs represent a treatment option for people with diabetic retinopathy and are routinely used to treat various other eye conditions. However, anti-vascular endothelial growth factor drugs are expensive relative to current care options, and it is unclear whether this additional cost is justified when the immediate risk of vision loss is lower compared to patients with more aggressive ophthalmological conditions. Objective To systematically review the evidence supporting the cost-effectiveness of alternative treatments for diabetic retinopathy. Methods A systematic review of all comparative cost-effectiveness studies evaluating any treatment for diabetic retinopathy was conducted. Bibliographic searches were carried out to identify studies reporting on the cost-effectiveness of treatments for diabetic retinopathy; the latest searches were conducted on 28 April 2023. Included studies were synthesised narratively and evaluated with reference to UK decision-making. Studies were grouped by population into non-proliferative diabetic retinopathy and proliferative diabetic retinopathy. Results The review identified five studies in the proliferative diabetic retinopathy population, all of which examined the cost-effectiveness of anti-vascular endothelial growth factor treatments compared to pan-retinal photocoagulation. Results of these studies suggest that anti-vascular endothelial growth factor treatments offer some additional benefits in terms of preserved visual acuity but also incur substantial additional costs relative to pan-retinal photocoagulation. Most authors agreed that the additional costs outweigh the limited benefits, especially in certain patient subgroups without pre-existing oedema. As most of the identified evidence considered a US perspective, it is unclear how these results would translate to a UK setting. Two studies were identified in the non-proliferative diabetic retinopathy population. There was limited evidence to support the early use of anti-vascular endothelial growth factor treatment. However, one UK study suggested that early treatment of non-proliferative diabetic retinopathy with pan-retinal photocoagulation is cost-effective compared to delayed pan-retinal photocoagulation. Conclusions Overall, there is a dearth of cost-effectiveness evidence considering the UK context. The identified studies raised doubts about the cost-effectiveness of anti-vascular endothelial growth factor treatments for proliferative diabetic retinopathy. No conclusions can be made regarding the cost-effectiveness of anti-vascular endothelial growth factor treatments for non-proliferative diabetic retinopathy. Future research should focus on developing rigorous model-based cost-effectiveness analyses integrating all available evidence. Funding This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme as award number NIHR132948. Plain language summary Anti-vascular endothelial growth factor medications have been proposed as a treatment for diabetic retinopathy, a common complication of diabetes. In the United Kingdom, the usual treatment for diabetic retinopathy is currently pan-retinal photocoagulation, commonly known as laser therapy. While there is evidence supporting the effectiveness of anti-vascular endothelial growth factor medications for managing diabetic retinopathy, it is unclear whether they represent good value for money. This study aims to review the existing evidence on the cost-effectiveness (value for money) of treatments for diabetic retinopathy by systematically searching for relevant studies and collating the findings. The results of our review consider two types of diabetic retinopathy: non-proliferative and proliferative. In patients with proliferative diabetic retinopathy, we found five studies that compared anti-vascular endothelial growth factor medications with laser treatment. These studies suggest that anti-vascular endothelial growth factor medications may help preserve vision but are also more expensive than laser therapy. The authors of these studies expressed doubts about the cost-effectiveness of anti-vascular endothelial growth factor medications. A limitation of most of the studies identified in the review is that they were conducted in the United States, making it challenging to apply their findings to the UK healthcare context. In patients with non-proliferative diabetic retinopathy, we identified two studies. One compared anti-vascular endothelial growth factor medications with laser therapy but did not provide their findings in a way that could be interpreted. The other study, conducted in the United Kingdom, suggested that early use of laser therapy may help preserve vision and save money. This second study, however, did not investigate the possibility of using anti-vascular endothelial growth factor medications. Overall, we found few studies evaluating the cost-effectiveness of treatments for diabetic retinopathy. Further research is needed to understand whether anti-vascular endothelial growth factor medications are likely to represent value for money in the United Kingdom.